Využitelnost agregované flexibility pro řízení ES ČR - Mamula O.; Hrycej D.; Pittner T.; Střelec M.; Kasl F. (AF POWER agency a.s., 2020)
V jednotlivých scénářích budoucího vývoje energetiky je deficit instalovaného výkonu ve větší či menší míře nahrazován zdroji obnovitelnými, plynovými či jadernými. Mění se i chování spotřebitelů, část instalovaného výkonu se alokuje dovnitř odběrných míst. Rozkolísanost zatížení umocní rozvoj elektromobility. Článek pojednává o flexibilitě typu "výkon" využitelné pro agregaci do služeb výkonové rovnováhy.

In individual scenarios for future energy developments, the installed power deficit in the replaced to a greater or lesser extent by renewable, gas or nuclear sources. Consumer behaviour also changes, part of the installed power is allocated inside the sampling points. The viability of the load will increase the development of electromobility. The article deals with the flexibility of the type "power" usable for aggregation into balancing services.
Utilisation of aggregated flexibility for the grid controll
Keywords: aggregation; flexibility; ancillary services